The Correlation of Time Span of Suffering and Anxiety Level in Patient with Diabetes Melitus - Dedi Irawandi (Indonesian Contemporary Nursing Journal, 2020)
Introduction: Diabetes mellitus is a group of heterogeneous disorders characterized by an increase in glucose levels in the blood or hyperglycemia. Prolonged diabetes mellitus can cause serious problems both physically and psychologically. This study aims to analyze the correlation between diabetes mellitus illness and patient anxiety level. Method: This study used a cross sectional study with 38 respondents who were people with diabetes mellitus in the work area of the Kebonsari Health Center in Surabaya. The sampling technique used is purposive sampling. Anxiety level was measured using the Hamilton Rating Scale for Anxiety (HARS) questionnaire. Data were then analyzed using Spearman’s Rho statistical correlation test. Result: There is a significant correlation between the length of suffering from diabetes mellitus with the level of anxiety of sufferers in the work area of the Kebonsari Health Center in Surabaya (p value = 0,000). Conclusion: There is a significant relationship between the length of suffering from diabetes mellitus with anxiety levels of sufferers. For people with diabetes mellitus is expected to always think positively about everything that happens in themselves, so that it can produce adaptive coping in living life with a state of diabetes mellitus